Upgrading the Capacity of Local Community and Tourism Branding in Pagar Jaya Village - Rahman, Yudha; Kurnianingsih, Nela Agustin; Putri, Marsista Buana; Wiguna, Anindita Nanda; Rahmadinanti, Nabila Azahara; Soﬁani, Nita; Raihan, Ahmad; Ramadhan, Khalid Ahmad; Falyajaya, Fatthah Ikhwan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
Pagar Jaya Village is a coastal area at the southernmost tip of Sumatra Island and isolated in Punduh Pidada District, Pesawaran Regency, Lampung becoming one of the tourism villages in Lampung that has two main problems poor accessibility and low capacity of the community. As a result of this problem, the